2016
DOI: 10.1097/sap.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Sternocleidomastoid Flap Helps Reduce Complications After Free Jejunal Flap Reconstructions in Total Laryngectomy and Cervical Esophagectomy Defects

Abstract: Reconstruction of pharyngoesophageal defects can be technically challenging and requires extensive planning and careful execution. The free jejunal flap restores alimentary continuity with good functional outcomes. Fistula rates may be decreased with the use of a prophylactic SCM flap to reinforce the jejunal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…These include: complex osteomuscular flaps taken with partial thickness clavicular bone for mandibular reconstruction; myocutaneous flaps for oral defects; split flaps that take only the sternal or clavicular head to avoid excess bulk; and conventional myofascial flaps to reinforce jejunal free flap anastomoses following laryngectomy, or cover the carotid in malnourished patients undergoing modified radical neck dissection. 7,8,10,17,20,33,34…”
Section: Resultsmentioning
confidence: 99%
“…These include: complex osteomuscular flaps taken with partial thickness clavicular bone for mandibular reconstruction; myocutaneous flaps for oral defects; split flaps that take only the sternal or clavicular head to avoid excess bulk; and conventional myofascial flaps to reinforce jejunal free flap anastomoses following laryngectomy, or cover the carotid in malnourished patients undergoing modified radical neck dissection. 7,8,10,17,20,33,34…”
Section: Resultsmentioning
confidence: 99%
“…This case is unique on account of a severe TAF, TGCF and other postoperative complications such as tracheostenosis. In the past, Moody et al found the use of the sternocleidomastoid(SCM) flap helped repair laryngectomy and cervical oesophagectomy defects [29]. Nakajima et al also revealed SCM flap repair was an effective and minimally invasive treatment method for cervical anastomotic leakage after oesophagectomy [30].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that this flap reinforcement reduces fistula formation, and one study found SCM reinforcement reduces stricture formation at anastomotic sites. 48,49 Enteric tissue transfer has been subject to some criticism, including resulting speech having a "wet" quality, worse short-term swallowing outcomes, and high donor-site morbidity. 47,[50][51][52] However, recent meta-analyses have found no significant differences in donor-site morbidity or speech and swallowing rates when comparing jejunal flaps and FCFF.…”
Section: Tubed Reconstructionmentioning
confidence: 99%